Resztki kostne z grobów eneolitycznych ze skurczonemi szkieletami w Białym Potoku (w pow. czortkowskim) - Stojanowski, Karol (1895–1947) (Polskie Towarzystwo Prehistoryczne, 1926)
ill. ; 29 cm
Keywords: Eneolithic -- Poland; Eneolithic burials; human skeletal remains; physical anthropology; anthropological analysis; Biały Potok, Czortków district (Ukraine)

Czaszka z wczesnego okresu żelaza ze Słupcy - Gładykowska-Rzeczycka, Judyta (1928– ) (Zakład Narodowy im. Ossolińskich, 1958)
ill. ; 29 cm
Keywords: early Iron Age -- Poland; early Iron Age strongholds; human bone remains; anthropometry; Słupca, wielkopolskie voivodeship (Poland)

Pars pro toto i monosandalizm (na kanwie monografii Thorsberger Moor) - Baranowski, Tadeusz (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2018)
Weapon offering deposits have been discovered on peat-bog cult sites from the Roman period in Denmark and Germany; Thorsberger Moor near Schlezwig is one of the better known sites of this kind. Publications are useful for in-depth analysis and interpretation of different aspects of culture. Intentionally destroyed weapons of defeated enemies are believed to have been deposited as offerings. One example of this way of thinking in reference to Thorsberg is the presence, almost without exception, of the left shoes. This example of monosandalism, which appears in different cultures starting with the ancient Greeks, is not pars pro toto evidence of human offerings, especially in view of finds of this kind from Alken Enge near Illerup Ådal
24 cm
Keywords: Scandinavia; Thorsberger Moor; Illerup Ådal; Alken Enge; peat-bog offering sites; weapon offerings; human offerings; monosandalism

Znalezisko szkieletowe w Michałowicach koło Krakowa - Ginter, Bolesław (1938– ) (Polska Akademia Nauk. Instytut Archeologii i Etnologii, 1992)
P. 239-151 : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Neolithic -- Poland; Danubian cultures; Neolithic skeletal burials; human skeletal remains; anthropological analysis; Michałowice (Poland)

Obiekt schyłkowej (łódzkiej) fazy kultury trzcinieckiej w Dwikozach, woj. Tarnobrzeg - Ścibior, Jolanta (Zakład Narodowy im. Ossolińskich, 1980)
P. 95-124 : ill. ; 25 cm
English summary
Bibliography p. 121-123
Keywords: Bronze Age -- Poland; Trzciniec culture; Trzciniec culture settlement; Trzciniec culture pottery; human skeletal remains; Dwikozy (Poland)

Ludzkie szczątki kostne z grobów nr II, IV i VI na stanowisku 25 w Moroczynie, woj. Zamość - Gąsiorowski, Adam (Zakład Narodowy im. Ossolińskich, 1988)
P. 309-319 : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Roman period -- Poland; Masłomęcz group; Masłomęcz group cemeteries; human skeletal remains; anthropological analysis; Moroczyn (Poland)

Neolityczny szkielet ludzki z Sandomierza, woj. Tarnobrzeg - Wojdanowicz, Kamila (Zakład Narodowy im. Ossolińskich, 1989)
P. 143-157 : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Neolithic -- Poland; Bell Beaker culture; Bell Beaker culture graves; human skeletal remains; anthropological analysis; Sandomierz (Poland)

Uwagi na marginesie ekspertyzy kości pochodzących z kurhanu nr 15 w Izbicku, woj. Opole - Magnuszewicz, Michał (Zakład Narodowy im. Ossolińskich, 1977)
P. 177-178 ; 25 cm
English summary
Bibliographical footnotes
Keywords: early Middle Ages -- Poland; early medieval barrows; human skeletal remains; anthropological analysis; Izbicko (Poland)

Wyniki badań przepalonych szczątków kostnych z cmentarzyska kurhanowego ludności kultury pomorskiej w Marcinowie, woj. Zielona Góra - Piontek, Janusz (Zakład Narodowy im. Ossolińskich, 1976)
P. 197-202 : ill. ; 25 cm
English summary
Keywords: Hallstatt period -- Poland; Pomeranian culture; Pomeranian culture barrow cemeteries; human skeletal remains; anthropological analysis; Marcinów (Poland)

Sprawozdania Archeologiczne T. 25 (1973), Sesje i konferencje - Zoll-Adamikowa, Helena (1931–2000) (Zakład Narodowy im. Ossolińskich, 1973)
Sympozjum "Metody, wyniki i konsekwencje badań kości z grobów ciałopalnych"
P. 369-371 ; 25 cm
Keywords: archaeological conferences; methodology of archaeology; cremation burials; human skeletal remains; anthropological research

Analiza antropologiczna wczesnośredniowiecznych pochówków ciałopalnych z kurhanów 3, 10 i 15 w Kornatce, pow. Myślenice - Wiercińska, Alina (Zakład Narodowy im. Ossolińskich, 1974)
P. 197-203 ; 25 cm
English summary
Bibliographical footnotes
Keywords: early Middle Ages -- Poland; early medieval cremation barrows; human skeletal remains; anthropological analysis; Kornatka (Poland)

Analiza antropologiczna wczesnośredniowiecznych pochówków ciałopalnych z kurhanów 1, 4 i 7 w Kornatce, pow. Myślenice - Kaczanowski, Krzysztof (Zakład Narodowy im. Ossolińskich, 1974)
P. 187-195 : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: early Middle Ages -- Poland; early medieval cremation barrows; human skeletal remains; anthropological analysis; Kornatka (Poland)

Analiza antropologiczna wczesnośredniowiecznych pochówków ciałopalnych z Guciowa, pow. Zamość - Kaczanowski, Krzysztof (Zakład Narodowy im. Ossolińskich, 1974)
P. 183-185 ; 25 cm
English summary
Keywords: early Middle Ages -- Poland; early medieval cremation burials; human skeletal remains; anthropological analysis; Guciów (Poland)

Analiza antropologiczna neolitycznego pochówka szkieletowego z Kietrza, pow. Głubczyce - Kaczanowski, Krzysztof (Zakład Narodowy im. Ossolińskich, 1974)
P. 41-43 ; 25 cm
English summary
Bibliographical footnotes
Keywords: Neolithic -- Poland; Corded Ware culture; Corded Ware culture graves; human skeletal remains; anthropological analysis; Kietrz (Poland)

Analiza antropologiczna materiałów kostnych z cmentarzyska kultury ceramiki sznurowej w Koniuszy, woj. Kraków - Gleń, Elżbieta (1949– ) (Zakład Narodowy im. Ossolińskich, 1979)
P. 79-90 : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Neolithic -- Poland; Corded Ware culture; Corded Ware culture cemeteries; human skeletal remains; anthropological analysis; Koniusza (Poland)

Identyfikacja antropologiczna pochówków z osady pucharów lejkowatych (KPL) w Sarnowie (stan. 1A), woj. Włocławek - Kapica, Zdzisław (1928– ) (Zakład Narodowy im. Ossolińskich, 1986)
P. 91-107 : ill. ; 25 cm
English summary
Bibliographical footnotes
Bibliography p. 106
Keywords: Neolithic -- Poland; Funnel Beaker culture; Funnel Beaker culture graves; human skeletal remains; anthropological analysis; Sarnowo (Poland)

Les progres de l'homme - Hocart, Arthur Maurice (1883–1939) (Payot, 1935)
358, [1] p. ; 22 cm
Onomastical index
Bibliographical footnotes
Keywords: social anthropology; cultural anthropology; history of civilizations; history of man; history of culture; human cultural evolution; development of technology

Ekspertyza antropologiczna materiałów ciałopalnych z cmentarzyska w Dobrzeniu Małym, woj. Opole - Rajchel, Zbigniew (Zakład Narodowy im. Ossolińskich, 1978)
P. 93-96, [1] folded leaf : ill. ; 25 cm
English summary
Bibliographical footnotes
Keywords: Bronze Age -- Poland; Lusatian culture; Lusatian culture cemeteries; human skeletal remains; anthropological analysis; Dobrzeń Mały (Poland)

Anthropological analysis of a skeleton of the Lublin-Wołyń culture from Książnice, site 2, the Pacanów Commune, the county of Busko Zdrój - studies conducted in 2004 - Haduch, Elżbieta (1949– ) (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2006)
P. 293-301, [1] leaf of photos : table ; 25 cm
Bibliography p. 297
Text paralel in English and Polish
Keywords: Neolithic -- Poland; Lublin-Volhynian culture; Lublin-Volhynian culture graves; human skeletal remains; anthropological analysis; Książnice (Poland)

Szkielet ludzki z mezolitycznego grobu z Kamieńskich, stan. 1, gm. Orzysz, woj. suwalskie - Kozłowski, Tomasz (Polska Akademia Nauk. Instytut Archeologii i Etnologii, 1998)
P. 131-134 : ill. ; 25 cm
English summary
Bibliography p. 133
Keywords: Mesolithic -- Poland; Mesolithic skeletal graves; human skeletal remains; anthropological analysis; Kamieńskie, Orzysz commune (Poland)

Anthropological analysis of skeletons of Lublin-Volhynian Culture from Książnice, site 2,commune Pacanów, district Busko Zdrój - Haduch, Elzbieta (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2004)
P. 261-270, [1] leaf of photos : tables ; 25 cm
Bibliography p. 266
Text paralel in English and Polish
Keywords: Neolithic -- Poland; Lublin-Volhynian culture; Lublin-Volhynian culture graves; human skeletal remains; anthropological analysis; Książnice (Poland)

Szkielety z cmentarzyska kultury ceramiki sznurowej w Łękawie, woj. świętokrzyskie - analiza antropologiczna - Haduch, Elzbieta (Polska Akademia Nauk. Instytut Archeologii i Etnologii, 1999)
P. 181-190 : ill. ; 25 cm
English summary
Bibliography p. 188-189
Keywords: Neolithic -- Poland; Corded Ware culture; Corded Ware culture cemeteries; human skeletal remains; anthropological analysis; Łękawa (Poland)

Human bones from 13(?)-17th cent. cemetery from Busówno in the light of anthropological analysis - Borowska-Strugińska, Beata (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2008)
P. 369-379 : tables ; 25 cm
Bibliography p. 374
Text paralel in English and Polish
Keywords: Middle Ages-modern period -- Poland; medieval-modern period cemeteries; human skeletal remains; anthropological analysis; Busówno (Poland)

[A dachshund] [An iconographic document] - [Bogdanowicz, Mikołaj] (1914)
The photograph shows a dog (breed dachshund) with a dark coat, sitting on the stone wall
The author of the photograph was the father of the photo owner. He was an engineer - building roads and bridges (a specialization in the former KK Austria), Mikołaj Bogdanowicz. During the 1st World War, as a native of Galicia, he was appointed to the Austrian army. In this army he was the commander of three companies of engineers, one of whom was a Jewish company. The area of its operation was Volhynia and partially Podolia, where during many months of "stopping" of the front he was building trenches, roads, bridges, etc.
the period of 1st World War, Podolia, now Ukraine
The photo sent to the contest named “Photography of the Polish village pre-1948” organized in 1983 by the quarterly “Fotografia” (Photography) and the weekly “Nowa Wieś” (New village). Copy of the photo kept at the Institute of Archaeology and Ethnology of the Polish Academy of Sciences (former Institute for the History of Material Culture)
Keywords: ethnography; material culture; social culture; animal; dog; human-nature relations; Podolia (Ukraine)

Human burials and funeral rites of the Linear Pottery culture from the territory of Poland - Czekaj-Zastawny, Agnieszka (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2021)
Human burials of the Linear Pottery culture in Poland are not common. The recent discovery in Modlniczka of the first – and thus far the only – LBK cemetery in Poland was therefore a significant one. Presently, there are only 17 other known sites with burials. Thirteen sites are in south-eastern Poland, four in Kuyavia, and one in the Odra River valley. In comparison with other burial sites in Central and Western Europe, the graves of the LBK in Poland do not provide many clues about the funerary customs of this culture. Their small number and the very limited proportion of preserved human remains make it impossible to perform many types of analyses. However, despite the small amount of evidence, we can observe general patterns, which are typical of the entire European LBK – in terms of both settlements and burials
ill. ; 25 cm
Keywords: Early Neolithic; Linear Pottery culture; funeral rite; human burials; Vistula river basin